RETRACTED: A novel mathematical model for the effects of wall properties on pumping flow of a biofluid in a symmetrical three-dimensional curved duct - Alfwzan, Wafa F.; Riaz, Arshad; Alammari, Maha; Hejazi, Hala A.; Tag El-Din, ElSayed M. (Frontiers in Physics, 2023)
Most pumping actions entail a physical volume change of the duct, which is frequently achieved by a compliant wall or membrane. In the current study, a mathematical model has been developed to analyze a peristaltic transport of a Newtonian fluid in a bended duct with rectangular face and compliant walls for the first time in literature. The walls of the duct are supposed to be flexible. Such geometries are most commonly used in clinical and biological equipment. Flexible ducts are more useful than rigid one, which doesn’t require an extra struggle for supplement, vandalizing or accessary variations. Here, authors have used the limitations of lubrication theory to construct the conclusive model. A well know perturbation technique is incorporated to handle the Navier-Stokes equations. A concentration is kept on various aspect ratios and the curvatures. A system of curvilinear coordinates followed by the cylindrical system is taken into account to represent the mathematical problem. No-slip boundary limitations are considered at the walls along with an extra constraint of compliant walls showing damping force and walls stiffness. Graphical discussion is made in a comprehensive way to examine the effect of all emerging factors of the study in both two and three dimensional display. It is found that large curvature and flexure rigidity decreases the fluid velocity uniformly but aspect ratio and amplitude parameters can promote the fluid velocity. A validation of the results is measured through providing residual error curve. The current readings are compared with the straight duct to make a comparison with the existing literature.